Fenologia reprodutiva de Prunus myrtifolia (L.) Urb. e Casearia sylvestris Sw em clima subtropical no Sul do Brasil - Pissatto, Mônica (2016)
The rhythm of flowering, fruiting, flushing and leaf fall is characteristic of each species and varies depending on weather conditions. Among the meteorological factors of greater influence on plant phenology are the air temperature, the day length and water variations. The phenological study provides basic information for management and conservation of the species and makes it possible to understand the relationship between the growth and development of plants and meteorological factors. The objectives of this study were to characterize the reproductive phenological pattern of a population of Prunus myrtifolia (L.) Urb. and a population of Casearia sylvestris Sw in Santa Maria, Rio Grande do Sul and the relationship of the reproductive phenophases with the air temperature and the day length annual variation. Phenological observations were carried out fortnightly in 10 plants of each species, selected randomly, located in the Botanical Garden of the Federal University of Santa Maria (UFSM), (29º42'S; 53º42'W; 90). The period of the study was from July 2013 to December 2015 to C. sylvestris and from August 2010 to September 2014 for P. myrtifolia. The phenofases observed were flower buds, anthesis, unripe fruits and ripe fruits. The characterization of reproductive phenology pattern of the populations was performed using the phonological Indexes of Fournier and Activity. For both species were analyzed the relation between the annual variation of the phenological indexes with the meteorological factors. In addition was performed analysis of heat sum, photothermal units and variation of flowering day length to find which of these factors is determinant of flowering induction in this species. The main episode of flowering for P. myrtifolia occurred from July to November with greater intensity and activity from August to October. Fruiting occurred from September to February, with greater levels of activity and intensity of unripe fruits from October to December and of ripe fruit from December to January. The flowering time of the population of C. sylvestris was from June to November. The flower buds showed sharp increase in the levels of intensity and activity during the transition from July to August, occurring its greatest expression in August and September. Anthesis was observed from July to October, with pronunced and abrupt increase in the levels of intensity and activity during the transition from August to September, with its greater expression in mid-September for all the years observed. The fruits occurred mainly in October and November, both unripe and ripe. Species showed seasonal phenological pattern with annual flowering and fruiting. The results showed that the increase in day length which starts after the winter solstice is crucial in flowering induction for this species. The astronomical factor proved to be a more reliable predictor of the flowering initiation date than the heat sum and the photothermal units. In both cases fructification occurred in the period of the year with higher air temperatures and longer days. Therefore, the photoperiodic response of the plants ensures that the fruiting takes place in a period with great availability of energy.